Magnifying endoscope with NBI to predict the depth of invasion in laryngo‐pharyngeal cancer. (24th November 2014) - Tateya, Ichiro; Morita, Shuko; Muto, Manabu; Miyamoto, Shin'ichi; Hayashi, Tomomasa; Funakoshi, Makiko; Aoyama, Ikuo; Hirano, Shigeru; Kitamura, Morimasa; Ishikawa, Seiji; Kishimoto, Yo; Morita, Mami; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To examine if macroscopic classification with a magnifying gastrointestinal endoscope with narrow band imaging (ME‐NBI) is useful in predicting pathological depth of tumor invasion in laryngo‐pharyngeal cancer. Study Design Retrospective study. Methods Preoperative endoscopy reports and postoperative pathological reports on 139 laryngo‐pharyngeal cancer lesions were retrospectively reviewed, and the association between macroscopic findings in the lesions and the depth of tumor invasion was analyzed statistically. Results The ratios of lesions macroscopically classified as 0‐I (superficial and protruding), 0‐IIa (slightly elevated), 0‐IIb (true flat), 0‐IIc (slightly depressed), and 0‐III (superficial and excavated) in the preoperative endoscopy reports were 3%, 25%, 71%, 1%, and 0%, respectively. Regarding the depth of tumor invasion in the postoperative pathological reports, the ratios of lesions classified as EP (carcinoma in situ), SEP (tumor invades subepithelial layer), and MP (tumor invades muscularis propria) were 73%, 26%, and 1%, respectively. The ratios of subepithelial invasion or muscular invasion in 0‐I, 0‐IIa, and 0‐IIb were 100%, 54%, and 14%, respectively, and showed significant difference (P < 0.0001). Only one of 139 lesions invaded the muscular propria. Conclusions This study is the first one to show that macroscopic findings by ME‐NBI predict the depth of tumor invasion in superficial laryngo‐pharyngeal cancer. It was indicated that there is a little chance of muscular invasion if the lesion is endoscopically diagnosed as 0‐I or 0‐II. A new T stage classification based on the depth of tumor invasion may be needed in order to adapt the classification to include transoral surgery. Level of Evidence 4 Laryngoscope, 125:1124–1129, 2015